Critical Tracing of Arabic Language Acquisition in Indonesian Context - Suci Ramadhanti Febriani; Ayu Desrani; Arifka Mahmudi; Kddour Guettaoui Bedra; Zainul Arifin (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2022)
This study aimed to explore how Arabic phonological, vocabulary, and grammatical are acquired. A qualitative approach was used to deeply explore that acquisition. The results showed that the strategy of acquiring phonological aspects carried out by drilling audio listening activities, either in the form of lectures from native speakers directly or in the form of murottal, Netflix, YouTube, and online radio; while the vocabulary acquisition strategy is done by using an Arabic dictionary both online and offline, as well as reading more books, and news through online portals. Grammatical elements are acquired by directly reading nahwu and shorof books such as Jurumiyyah, Nahwu Wadhih, and Al-arabiyah baina yadaik practicing directly by studying Arabic sentences and practicing I'rab. The findings showed that the language acquisition process using various strategies can provide language acquisition of phonological, vocabulary, and grammatical aspects. Practical implications and further research to explore more diverse variables and more complex research methods are provided.